Penggunaan Metode Pembelajaran Berbasis Permainan Untuk Meningkatkan Hasil Belajar Siswa Dalam Materi Bilangan Pecahan Pada Kelas V SDN Telang II - Dzakiyatul Mumtazah; Dewi Fitrianingsih; Salsabil 'Aqiilah (Yayasan Pondok Pesantren Nurul Islam Mojokerto, 2023)
This study aims to determine the extent to which student’s understanding of mathematics subjects, especially fraction material and improve student learning outcomes in mathematics using game method through the snakes and ladders game which is carried out at SDN II Telang, Kamal, Bangkalan which is held from April to in May 2023. The methods used in this study were interview, observation, and documentation methods, and the design or research design used was a form of Classroom Action Research. The results of the study were that during pre-cycle students took tests with an average score of 75, cycle 1 of 80.5, cycle II of 91. From the results above it can be concluded that there was an increase in student learning outcomes in mathematics, especially number material fractions using the game method through the snakes and ladders game.